Evaluation of the competitive ability of four wheat (Triticum aestivum L.) cultivars with weeds and its effect on growth characteristics, yield and its components - Ammar, Jassim Al-Khaz'ali; Naeem, A Mutlag; Khudeir, A Salman; Alaa, F Alhameedawi; Aswad, H Aswad; Ibrahim, E El-Beially (Plant Science Today, 2026)
A field experiment was conducted at the Abu Ghraib Research Station during the 2022 and 2023 seasons using a split-plot experiment laid out in a randomized complete block design (RCBD) with three replications. The study aimed to assess the competitive ability of four wheat cultivars (Buhuth 22, Buhuth 10, Baghdad and Ibaa 99) against weeds and their effects on growth traits, yield and its components. The experiment included four weed competition treatments: complete weed removal, removal of narrow-leaved weeds, removal of broad-leaved weeds and no weed removal. The results showed that weed removal improved all studied traits, with the weed-free treatment recording the highest plant height (92.0 cm), number of spikes (407.1 spikes m-2), 1000-grain weight (38.95 g) and grain yield (6.33 tons ha-1). In contrast, full weed competition led to a reduction in these values by up to 45 %. The Buhuth 22 cultivar outperformed others in most yield traits, recording the highest grain yield (5.52 tons ha-1), whereas Buhuth 10 had the lowest productivity (3.71 tons ha-1). Additionally, cultivars with rapid growth and high density exhibited greater competitiveness against weeds, minimizing their negative impact on growth and productivity. The removal of either narrow- or broad-leaved weeds had a similar effect in reducing competition and enhancing growth, though the completely weed-free treatment achieved the best results. The study recommends adopting highly competitive cultivars such as Buhuth 22 and enhancing weed control through dense planting and integrated management practices. This combined strategy promotes sustainable wheat productivity, minimizes herbicide dependence and ensures efficient resource utilization for achieving high yields under weed-infested conditions.